Effect of Supplementation of Synthetic Serum Substitutes Versus Fetal Bovine Serum in Maturation Media on In Vitro Maturation of Oocytes from Sahiwal Cows - Singh Sandhu, Gurbeer; Singh, Narinder; Singh, Khushpreet; Kaur Mavi, Gurjot; Singh Malik, Vijay; Singh, Navdeep; Saini, Neetu (The Indian Journal of Animal Reproduction, 2026)
The outcome of in vitro embryo production (IVEP) is dependent on the successful oocyte maturation. The composition of mat uration media plays an important role in higher proportion of oocyte reaching metaphase II stage. Fetal bovine serum (FBS) is a common supplement, though, its use is associated with inconsistency and ethical issues. Hence, this investigation compared two defined alternatives media (KnockOut Serum Replacement (KSR) and NuSera) to FBS for in vitro maturation (IVM) of Sahiwal cattle oocytes. Cumulus-oocyte complexes (COCs) were collected via ovum pick-up and cultured in media containing 10% KSR, 10% NuSera, 5% FBS, or no supplement. The media supplemented with 10% NuSera revealed the 85.92% full cumulus cell expansion which was equivalent to the media supplemented with 5% FBS revealed 90.41% cumulus cell expansion. While, 10% KSR revealed only 21.74% full cumulus cell expansion. The findings of the present study indicates that 10% NuSera could be a viable synthetic substitute for FBS in the IVM of bovine oocytes.